Assessing the ecosystem services provided by urban green spaces along urban center-edge gradients - Chang, Jie; Qu, Zelong; Xu, Ronghua; Pan, Kaixuan; Xu, Bin; Min, Yong; Ren, Yuan; Yang, Guofu; Ge, Ying (Scientific reports, 2017)
Urban green spaces provide various ecosystem services, especially cultural services. Previous assessment methods depend either on hypothetic payments for ecosystems or real payments not directly related to ecosystems. In this paper, we established a method for assessing the cultural ecosystem services in any location in urban area using only two variables, green space (ecosystem) and land rent (real payment). We integrated the cultural and the regulating services into the total ecosystem services because urban green spaces provide almost no provisioning services. Results showed that the same area of green spaces near the center provided much higher cultural services than that near the urban edge; the regulating services accounted for 5% to 40% of the total ecosystem services from the center to the edge of urban area; along the center-edge gradient, there was a threshold out which the ecosystem services were lower than the maintenance cost of green spaces.